Quantification of AgNOR expression in exfoliated oral mucosal cells of tobacco chewers with and without lesion - Anushree Sharma; Susmita Saxena (Wolters Kluwer Medknow Publications, 2012)
Background: Nucleolar organizer regions (NOR) are associated with proliferative activity and represent a diagnostic and prognostic marker. Materials and Methods: Smears were taken from smokers, tobacco chewers, oral squamous cell carcinoma patients, and normal subjects and evaluated by 2 silver-staining nucleolar organizer region (AgNOR) counting methods: (1) mean number of AgNORs per nucleus (mAgNOR); and (2) percentage of nuclei with >3 and >5 AgNORs (pAgNOR). Results: A statistically significant difference was observed between normal subjects, smokers, tobacco chewers, and oral cancer patients and between tobacco chewers with and without lesion. No significant difference was observed between tobacco chewers and smokers except in the percentage of >5 criteria. Conclusions: AgNOR enumeration using noninvasive methods, such as the cytobrush appears to be useful technique in distinguishing between normal mucosa, mucosa with and without lesions exposed to carcinogens, such as tobacco and frank oral carcinoma.